The Relationship between Student Perceptions of DeepSeek Use and Mathematics Learning Effectiveness - Naisela Kurnia Ananda; Hana Ni'matul Rizky; Nonik Indrawatiningsih; Yunita Nur Hasanah (Journal of Mathematical Pedagogy (JoMP), 2025)
This research uses descriptive quantitative survey research. This study aims to determine the relationship between student perceptions of using DeepSeek on the effectiveness of mathematics learning. The sample in this study were 100 students majoring in mathematics at Surabaya State University. The sampling technique was carried out by means of probability sampling technique, namely simple random sampling. The data source of this research is the result of a survey conducted on the sample. In this survey, researchers used a questionnaire regarding students' perceptions of the use of DeepSeek on the effectiveness of mathematics learning with a Likert scale analyzed using Pearson's correlation analysis. The results showed that the correlation analysis between the independent variable (student perceptions in using DeepSeek) and the dependent variable (the effectiveness of mathematics learning) revealed a strong and positive relationship between the two variables. This means that there is a fairly strong and positive relationship between student perceptions of using DeepSeek and the effectiveness of mathematics learning.